Quantum chemical study of NO reduction mechanism on Ag /Al2O3 catalysts - Ragoyja, Ekaterina G.; Matulis, Vitaly E.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2021)
It was shown that N2O content among NO reduction products increases with an increase of the silver concentration in the catalyst because the nature of the catalytic centers changes and leads to a subsequent change in the mechanism of the reaction. Two reaction mechanisms were proposed and studied by means of quantum chemistry: a two-stage mechanism that proceeds via NO dimer formation on catalysts with high (above 2 wt. %) silver concentration and a parallel mechanism with isocyanates involved on catalysts with low (below 2 wt. %) silver concentration. It was demonstrated that on catalysts with high silver concentration mechanism that involves stepwise NO reduction via N2O to N2 is realised. Moreover, the final stage is complicated by the fact that formed intermediates and N2O are likely to desorb from the catalyst surface. In the case of catalysts with low silver concentration, the formation of both products (N2O and N2) proceeds in parallel and the lower activation barriers of the reaction leading to N2, as well as the thermodynamic profitability of its formation, lead to the predominance of the target product. The competition between the proposed mechanisms was studied in the case of catalytic centers represented by silver dimers. It was shown that activation barriers of reaction proceeding via NO dimer formation are lower than the corresponding barriers of the reaction with isocyanates involved, which confirms the prevalent realisation of the first process and the predominance of N2O among the final products. The obtained results explain the experimental data and are significant for further modelling of the mechanism of nitrogen oxides catalytic reduction considering the Al2O3 support.